Q: What is the nth term of 7 12 17 22 27?

Write your answer...

5n - 3

The nth term is 5n-3 and so the next term will be 22

5

tn=5n-3

If you meant: 2 12 22 32 then the nth term = 10n-8

The sequence has a difference of 10, so the nth term starts with 10n. Then to get to -8 from 10 you need to subtract 18. So the nth term is 10n - 18.

The nth term is 22n and so the next number will be 5*22 = 110

It is: nth term = 29-7n

The nth term is 3n+7 and so the next number will be 22

The nth term is -7n+29 and so the next term will be -6

5=22+12 8=22+22 13=22+32 20=22+42 29=22+52 40=22+62

+9

Balls deep

1,7,13,19

6n+10

7n - 6

t(n) = (5n3 - 30n2 + 85n - 48)/6 , n = 1, 2, 3, ...

Assuming the pattern would continue: 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13...

4 10 16 22 28 34 40 ....... Each term is increased by 6 or nth term = 6n-2

3n+7

It means to find the generic expression for any term, not just for one specific term. For example, in the sequence 1, 4, 9, 16, 25... it should be clear that these are square numbers, which you can write as 12, 22, 32, etc. The nth. term is n2, meaning that for any number "n", term number n is n2.

One method is an = n2 +1.So the first term is 1+1the second is 22 +1=5the third is 32 +1=10the fourth is 16+1=17 etc.There is also a recursive way to find it. I only point it out so you can see there may be more than one way to denote the nth term in a sequence. This method uses recursion.2+0=2=a12+3=5=a25+5=10 =a310+7=17 =a417+9=26 =a526+11=37 =a6So nth term is easy recursivelynth term=an =an-1 +(2(n-1)+1) =an-1 +(2n-1) =for example n=4 is the 4th term.a4 =a3 +(8-1)=10+7=17the 5th term a5 =17+(2x5-1)=17+9=26

It is: -6n+22

You must mean what is the next number in the series, not the 'nth', which is undefined. The next number is 58.

17 + 5 = 22 17 - 5 = 12